A high temperature ceramic-based rock wool composite board and its preparation process

Through the combination process of ceramic powder, inorganic gelling materials and rock wool fibers, ceramic bedrock wool composite sheets are prepared, and new phases such as aluminum phosphate are generated through sintering, which solves the problem of poor thermal stability of existing materials in high-temperature environments, and improves the binding force, thermal stability and thermal cycling resistance between high-layers.

CN119751102APending Publication Date: 2025-04-04NANJING TONTECH ROCKWOOL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411951250.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing high-temperature ceramic bedrock wool composites have problems such as poor thermal stability, easy chemical structure decomposition, release of combustible gases and generation of residual carbon in high temperature environments, and flame retardant may release toxic gases after decomposing at high temperatures.

Method used

The combination process of ceramic powder, inorganic gelling materials and rock wool fibers is used to prepare ceramic bedrock wool composite sheets through vibration molding and sintering technology, and the temperature and time control are optimized during the sintering process to generate new phases such as aluminum phosphate to enhance interface binding force and thermal stability.

Benefits of technology

The interlayer bonding force, thermal stability and thermal cycling resistance of composite sheets are significantly improved, reducing the risks of interface cracking and peeling, while maintaining the lightweight and thermal insulation properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751102A_ABST
    Figure CN119751102A_ABST
Patent Text Reader

Abstract

The present application relates to a high-temperature ceramic-based rock wool composite board and its preparation process, wherein the composite board includes a ceramic base layer, a bonding layer and a rock wool fiber layer, and the three layers are efficiently combined by optimizing the thickness ratio and material formula. The ceramic base layer is prepared by mixing waste ceramic powder, high-aluminum cement and rock wool fiber, and the bonding layer is made of aluminum phosphate and rock wool fiber as the main raw materials. New phases such as aluminum phosphate and calcium aluminum phosphate are generated during the high-temperature sintering process, thereby significantly improving the interlayer bonding force and interface stability. The rock wool fiber layer provides lightweight thermal insulation performance, and by adding an appropriate amount, it matches the thermal expansion coefficient with the ceramic base layer to alleviate interface stress concentration. This process is simple and efficient, and the density and mechanical properties of the material are ensured by optimizing the sintering system. Compared with the prior art, the composite board of the present invention has excellent high temperature resistance, thermal cycle resistance and thermal insulation effect, and is widely used in the field of thermal insulation protection under high temperature environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite boards, and in particular to a high-temperature ceramic-based rock wool composite board and a preparation process thereof. Background Art

[0002] In recent years, with the rapid development of industrialization and modernization, thermal insulation, heat preservation and protection materials in high temperature environments have received extensive attention and research. Ceramic-based composite materials have become an important component of high-performance materials due to their excellent high-temperature stability, chemical corrosion resistance and mechanical strength. In the field of high-temperature thermal insulation, rock wool is widely used in construction and industry due to its low thermal conductivity, good sound insulation and lightweight properties. However, single ceramic-based materials usually have the problems of high density and heavy weight, while rock wool materials are easily limited by insufficient structural strength and poor chemical stability under high temperature conditions. Therefore, compounding ceramic-based materials with rock wool, which not only gives play to the high-temperature durability and mechanical properties of ceramics, but also takes advantage of the lightweight and thermal insulation advantages of rock wool, is one of the research hotspots in the field of materials.

[0003] The Chinese patent (application number: CN202410739797.0) discloses a high-strength fireproof rock wool board, which includes a fireproof layer and a thermal insulation layer from top to bottom; the raw materials of the fireproof layer include the following components by mass: rock wool fiber, first modified waste ceramic powder, epoxy resin, flame retardant, hydrophobic agent, curing agent; the raw materials of the thermal insulation layer include the following components by mass: rock wool fiber, second modified waste ceramic powder, epoxy resin, curing agent; the modified waste ceramic powder is waste ceramic powder modified by methyl dichlorophosphate and then by hydroxycarboxylic acid compounds. The above technical solution solves the problem of low strength of rock wool boards in the prior art. However, a large amount of organic components such as epoxy resin, curing agent and flame retardant are used in the formula. These materials usually show low thermal stability in high temperature environments, especially at high temperatures, and their chemical structures are prone to decomposition or thermal cracking. As an organic polymer material, the decomposition process of epoxy resin usually includes the breaking of molecular chains and the destruction of cross-linked networks, thereby releasing combustible gases such as carbon monoxide and methane, and generating residual carbon. Curing agents (such as amines or anhydride compounds) will also decompose or volatilize at high temperatures, further generating small molecular gases such as ammonia and carbon dioxide. The accumulation of these gases may not only participate in combustion, but also form pores inside the material, weakening its mechanical strength and density. In addition, although the flame retardant used in the formula can delay the combustion of the material to a certain extent, if it is a halogen or organophosphorus flame retardant, it will release toxic or corrosive gases such as hydrogen halides and phosphates after decomposition at high temperatures, which will not only pose a threat to the surrounding environment and personnel safety, but also may affect the long-term stability of the material. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation process of a high-temperature ceramic-based rock wool composite board, comprising the following technical steps:

[0005] Step S1. Prepare a ceramic base layer: weigh ceramic powder, a first inorganic gelling material and rock wool fiber according to a formula, mix the above raw materials in a blender to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use vibration molding to expel bubbles, let it stand for 2 to 4 hours for initial setting, and obtain a preliminarily shaped green body; Step S2. Prepare a bonding layer: weigh a second inorganic gelling material and rock wool fiber according to a formula and stir to form a bonding slurry, and apply the bonding slurry on the preliminarily shaped green body to form a bonding layer; Step S3. Prepare a rock wool fiber layer: weigh rock wool fiber, a first inorganic gelling material and ceramic powder according to a formula, mix the above raw materials in a blender to obtain a moldable rock wool fiber-based slurry, pour the rock wool fiber-based slurry on the bonding layer, use vibration molding to expel bubbles, let it stand for 2 to 4 hours for initial setting, and obtain a composite board green body; Step S4. Put the composite board green body into a sintering furnace for sintering to obtain a ceramic-based rock wool composite board finished product.

[0006] It should be noted that in step S1, the ceramic powder, the first inorganic gelling material and the rock wool fiber interact with each other to form a ceramic-based slurry. The first inorganic gelling material can undergo hydration or partial chemical coagulation reaction at room temperature or low temperature, providing a preliminary bonding "framework" for the ceramic powder and the rock wool fiber; the rock wool fiber is distributed in the slurry, which can enhance the toughness of the matrix through the "fiber bridging" mechanism. Vibration molding can remove bubbles in the slurry, making it denser and avoiding the appearance of internal holes or local stress concentration during the subsequent sintering process. Let it stand for 2 to 4 hours for initial coagulation, so that the slurry can obtain sufficient strength and dimensional stability to form a preliminarily shaped green body. In step S2, the second inorganic gelling material is mixed with the rock wool fiber to obtain a bonding slurry, and it is evenly coated on the surface of the preliminarily shaped green body to form a bonding layer. At this time, the second inorganic gelling material can be initially condensed and cured at a low temperature stage, bonded to the first layer of green body, and then provide a stable "transition layer" for the upper rock wool fiber-based slurry. In addition, the rock wool fiber plays a certain role in toughening and adjusting the thermal expansion coefficient in the bonding layer, reducing the interface cracks caused by the mismatch of the shrinkage of the upper and lower layers of materials during subsequent high-temperature sintering. In step S3, the rock wool fiber, the first inorganic gelling material and the ceramic powder are mixed into a rock wool fiber-based slurry and poured onto the bonding layer. At this time, the first inorganic gelling material continues to provide initial setting strength at low temperature, so that this newly cast layer can be quickly shaped. The rock wool fiber content in this layer is higher, bringing significant lightweight insulation function, and enhancing the material's crack resistance through the "fiber bridging effect". The ceramic powder provides a sintering skeleton for this layer in subsequent high-temperature sintering, and forms a compatible sintering system with the lower ceramic base part. Vibration molding helps to discharge bubbles in the newly poured slurry, reduce porosity and increase overall strength. It is then also necessary to stand for 2 to 4 hours for initial setting to obtain a green composite structure sufficient for handling or transfer. In step S4, the green composite sheet is sent to the sintering furnace for high-temperature sintering. The ceramic powder is sintered or partially liquid-phase sintered at high temperature, and chemically reacts or diffuses with the first and second inorganic cementitious materials at the interface, generating a ceramic phase or glass phase transition layer with high temperature stability; this makes the overall structure denser and the interlayer interfacial bonding strength is greatly improved. Rock wool fibers can maintain their fiber morphology within a reasonable firing temperature range to achieve toughening and heat insulation; if the temperature is high, some fibers and ceramic powder or cementitious materials generate a new composite phase to further improve thermal expansion matching. Through a reasonable insulation and cooling system, the organizational structure of ceramics and rock wool fibers gradually stabilizes, and a finished ceramic-based rock wool composite board with high temperature stability, lightweight insulation, and good interlayer bonding strength is obtained.

[0007] As a preferred technical solution for the preparation process of a high-temperature ceramic-based rock wool composite board, the first inorganic gelling material is high-alumina cement, and the second inorganic gelling material is aluminum phosphate.

[0008] It should be noted that high alumina cement generates calcium aluminate hydrates (such as CAH 10 , C2AH8), providing initial condensation and solidification for ceramic powder and rock wool fiber, so that the green body has sufficient strength and dimensional stability. At the same time, aluminum phosphate solidifies through chemical reaction in the bonding layer, forming a physical-chemical bond with high-alumina cement and the fiber surface, and realizing a stable preliminary connection between layers. During the high-temperature sintering process (800 to 1300°C), the hydration products of high-alumina cement decompose and generate high-temperature phases such as calcium aluminate (CA) and calcium aluminum spinel (CA6), which react synergistically with aluminum phosphate to generate a variety of new phases such as aluminum phosphate (AlPO4), calcium aluminum phosphate (CaAlPO4), etc. These newly generated phases have good thermal stability and chemical durability, and are distributed at the interface in the form of glass phase or semi-crystalline phase, which not only fills microcracks and pores, but also forms a "bridge" at the microstructural level, greatly enhancing the interlayer bonding strength. Moreover, on the one hand, these new phases usually have a thermal expansion coefficient between the ceramic matrix and the rock wool fiber matrix, playing the role of a "transition layer", gradually adjusting the thermal expansion gradient between the two materials in the microstructure, reducing the shear stress or tensile stress caused by expansion mismatch. On the other hand, the glass phase present in the new phase has a certain viscosity at high temperature, which can absorb and disperse local stress, and at the same time fill the interface microcracks by penetration, preventing crack propagation and enhancing the interface density. In addition, the viscosity and partial liquid properties of aluminum phosphate at high temperatures can buffer the interfacial stress concentration caused by the difference in thermal expansion coefficients between the ceramic matrix and the rock wool fiber gene, thereby reducing the risk of delamination or cracking.

[0009] As a preferred technical solution for the preparation process of a high-temperature ceramic-based rock wool composite board, in step S1, the ceramic powder is 50 to 70 parts, the first inorganic gelling material is 10 to 20 parts and the rock wool fiber is 15 to 30 parts.

[0010] It should be noted that the formula content in the ceramic base layer is optimized.

[0011] As a preferred technical solution for the preparation process of a high-temperature ceramic-based rock wool composite board, in step S2, the second inorganic gel material is 60 parts, and the rock wool fiber is 10 parts to 50 parts.

[0012] It should be noted that the formulation content in the bonding layer is optimized.

[0013] As a preferred technical solution for the preparation process of a high-temperature ceramic-based rock wool composite board, in step S3, the rock wool fiber is 40 to 60 parts, the first inorganic gelling material is 5 to 10 parts, and the ceramic powder is 10 to 20 parts.

[0014] It should be noted that the formula content in the rock wool fiber layer is optimized.

[0015] As a preferred technical solution for the preparation process of a high-temperature ceramic-based rock wool composite board, in step S4, the sintering system is firstly to heat up from room temperature to 200°C, at a heating rate of 1 to 2°C / min, and keep warm for 1 to 2h; then to heat up from 200°C to 500°C, at a heating rate of 2 to 3°C / min, and keep warm for 1 to 2h; then to heat up from 500°C to 800°C, at a heating rate of 2 to 5°C / min, and keep warm for 1h; then to heat up from 800°C to 1250°C, at a heating rate of 2 to 4°C / min, and keep warm for 1 to 3h; and finally, cool to room temperature with the furnace.

[0016] It should be noted that the temperature is raised from room temperature to 200°C, and the free water and part of the bound water in the green body are removed at a slow heating rate of 1 to 2°C / min to prevent the green body from cracking due to excessive steam pressure. At the same time, the temperature of each layer is evenly distributed through 1 to 2 hours of insulation to eliminate the internal temperature difference. Then, the temperature is raised from 200°C to 500°C, and the heating rate is increased to 2 to 3°C / min. This stage mainly completes the initial decomposition and solidification of high-alumina cement and aluminum phosphate, removes residual chemically bound water and possible organic matter, and provides thermal stability for the subsequent reaction of ceramic powder and inorganic cementitious materials. When the temperature is raised from 500°C to 800°C, the intermediate product of high-alumina cement is further decomposed at a heating rate of 2 to 5°C / min to generate a high-temperature phase of calcium aluminate; this stage promotes the initial sintering of ceramic powder and high-alumina cement through 1 hour of insulation, and ensures that the interface reaction begins to form a new bonding phase. Subsequently, the temperature is raised from 800°C to 1250°C, and the final firing temperature is reached at a heating rate of 2 to 4°C / min. At this stage, the calcium aluminate of the high-alumina cement reacts with aluminum phosphate to form new phases such as aluminum phosphate and calcium aluminum phosphate. The high-temperature insulation for 1 to 3 hours promotes the complete sintering of the ceramic powder and the densification of the new phases at the interface, significantly improving the interlayer bonding strength and reducing pores or defects. Finally, the furnace is cooled to room temperature. During the cooling process, the thermal stress is gradually released to avoid interface cracks or peeling caused by the large difference in thermal expansion coefficients between the ceramic matrix and the rock wool fiber matrix. The overall sintering system ensures the thermal expansion coordination, interface bonding strength and microstructural stability of each layer of the material by controlling the temperature, heating rate and insulation time in sections, thereby significantly improving the high-temperature performance and mechanical strength of the composite board.

[0017] As an optimal technical solution for the preparation process of a high-temperature ceramic-based rock wool composite board, the ceramic powder is waste ceramic powder.

[0018] It should be noted that by recycling waste ceramics and grinding them into granular powder, resource recycling can be achieved and production costs can be reduced. After crushing and grinding, the waste ceramics are refined to increase the specific surface area and improve the sintering activity. At the same time, they are more evenly mixed with high-alumina cement, aluminum phosphate and rock wool fibers, enhancing the interface bonding force and material density.

[0019] In addition, the present invention provides a composite board prepared by the above-mentioned preparation process, wherein the composite board includes a ceramic base layer, an adhesive layer and a rock wool fiber layer.

[0020] It should be noted that the ceramic base layer is the main load-bearing layer of the composite board. It is made of a mixture of ceramic powder, high-aluminum cement and rock wool fiber. After high-temperature sintering, it forms a dense ceramic structure, providing excellent high-temperature resistance and mechanical support. The bonding layer is located between the ceramic base layer and the rock wool fiber layer. It uses aluminum phosphate and rock wool fiber as the main components. The bonding layer not only provides preliminary chemical bonding at room temperature, but also forms a new phase of aluminum phosphate at high temperature, which significantly improves the interlayer bonding force, while buffering the thermal expansion difference between different materials to prevent interface cracking or peeling. The rock wool fiber layer is made of rock wool fiber, ceramic powder and high-aluminum cement. Its main function is to provide thermal insulation performance, while enhancing crack resistance and thermal shock toughness through the fiber bridging mechanism. The synergistic effect of the three-layer structure enables the composite board to have excellent mechanical properties, thermal stability and insulation effect in high-temperature environments. It is a high-performance, lightweight and high-temperature resistant material.

[0021] As a preferred technical solution for a composite board prepared by the above-mentioned preparation process, the thickness ratio between the ceramic base layer, the bonding layer and the rock wool fiber layer is (4 to 6): (0.5 to 1.5): (3 to 5).

[0022] It should be noted that the ceramic base layer is used as the main load-bearing layer, and its large thickness provides the mechanical strength and fire resistance required at high temperatures, while ensuring stable interface bonding through interaction with the bonding layer. The medium thickness of the bonding layer plays the role of a "transition layer", and its components (such as aluminum phosphate) generate new phases such as aluminum phosphate during high-temperature sintering, which can effectively fill the interface microcracks and relieve the stress difference between the ceramic base and the rock wool fiber base through the intermediate gradient of the thermal expansion coefficient. In addition, the thicker proportion design of the rock wool fiber layer provides excellent thermal insulation performance.

[0023] The present application provides a high-temperature ceramic-based rock wool composite board and its preparation process, which has significant beneficial effects. First, by optimizing the formula and thickness ratio of the ceramic base layer, the bonding layer and the rock wool fiber layer, the interlayer bonding strength and thermal stability of the composite board are significantly improved, ensuring its structural integrity under high temperature environment. Secondly, the new phases such as aluminum phosphate, calcium aluminum phosphate and phosphate glass phase generated in the bonding layer not only enhance the interfacial chemical bonding force, but also improve the density of the material by filling micropores, further improving the interface stability. In addition, the appropriate addition of rock wool fiber effectively alleviates the difference in thermal expansion coefficient between the ceramic base layer and the rock wool fiber layer, and reduces the risk of cracking caused by interfacial stress concentration during thermal cycling. Compared with the prior art, the composite board of the present application shows significant advantages in interlayer bonding strength, high temperature resistance and thermal cycle resistance. At the same time, it has the characteristics of light weight and heat insulation, which is suitable for the insulation and protection needs under high temperature environment, and provides an important reference and innovative solution for the field of high-performance composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a graph of the bonding layer of the composite board prepared in Example 2. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0028] It should be noted that the waste ceramic powder in this application comes from building ceramics, sanitary ceramics and refractory materials, and its chemical composition is shown in Table 1 below:

[0029] Table 1 shows the chemical composition of waste ceramic powder

[0030]

[0031] The waste ceramic powders used in the following examples and control examples are all from the same batch, ensuring the consistency of the chemical composition, particle size distribution and other physical properties of the raw materials. This control measure eliminates the performance fluctuations that may be caused by different sources of waste ceramic powders, ensuring the uniformity of experimental conditions and the comparability of data. By keeping the same batch of raw materials, the impact of different formulations, processes or structural designs on the performance of composite panels can be more accurately evaluated, ensuring the scientificity and reliability of the test results, thereby providing clearer guidance for optimizing formulations and processes.

[0032] Example 1

[0033] Embodiment 1 provides a high-temperature ceramic-based rock wool composite board and a preparation process thereof, wherein:

[0034] The high-temperature ceramic-based rock wool composite board comprises a ceramic base layer, a bonding layer and a rock wool fiber layer, wherein the thickness ratio among the ceramic base layer, the bonding layer and the rock wool fiber layer is 4:0.5:5.

[0035] Step S1. Prepare a ceramic base: weigh 60 parts of waste ceramic powder, 20 parts of high-alumina cement and 15 parts of rock wool fiber according to the formula, mix the above raw materials in a mixer to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use vibration molding to expel bubbles, let it stand for 2 hours for initial setting, and obtain a preliminarily shaped green body;

[0036] Step S2. Prepare a bonding layer: according to the formula, weigh 60 parts of aluminum phosphate and 30 parts of rock wool fiber and stir to form a bonding slurry, and apply the bonding slurry on the preliminarily shaped green body to form a bonding layer;

[0037] Step S3. Prepare a rock wool fiber layer: weigh 40 parts of rock wool fiber, 8 parts of high-alumina cement and 10 parts of waste ceramic powder according to the formula, mix the above raw materials in a mixer to obtain a moldable rock wool fiber-based slurry, pour the rock wool fiber-based slurry on the bonding layer, expel bubbles by vibration molding, let it stand for 2 hours for initial setting, and obtain a composite board green body;

[0038] Step S4. Place the green composite board into a sintering furnace for sintering to obtain a finished ceramic-based rock wool composite board, wherein the sintering system is to first heat the temperature from room temperature to 200°C at a heating rate of 2°C / min and keep warm for 2 hours, then heat the temperature from 200°C to 500°C at a heating rate of 3°C / min and keep warm for 1 hour, then heat the temperature from 500°C to 800°C at a heating rate of 2°C / min and keep warm for 1 hour, then heat the temperature from 800°C to 1250°C at a heating rate of 4°C / min and keep warm for 1 hour, and finally, cool to room temperature with the furnace.

[0039] Example 2

[0040] Embodiment 2 provides a high-temperature ceramic-based rock wool composite board and a preparation process thereof, wherein:

[0041] The high-temperature ceramic-based rock wool composite board comprises a ceramic base layer, a bonding layer and a rock wool fiber layer, wherein the thickness ratio among the ceramic base layer, the bonding layer and the rock wool fiber layer is 6:1:3.

[0042] Step S1. Prepare a ceramic base: weigh 70 parts of waste ceramic powder, 15 parts of high-alumina cement and 30 parts of rock wool fiber according to the formula, mix the above raw materials in a mixer to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use vibration molding to expel bubbles, let it stand for 4 hours for initial setting, and obtain a preliminarily shaped green body;

[0043] Step S2. Prepare a bonding layer: according to the formula, weigh 60 parts of aluminum phosphate and 30 parts of rock wool fiber and stir to form a bonding slurry, and apply the bonding slurry on the preliminarily shaped green body to form a bonding layer;

[0044] Step S3. Prepare a rock wool fiber layer: weigh 60 parts of rock wool fiber, 10 parts of high-alumina cement and 20 parts of waste ceramic powder according to the formula, mix the above raw materials in a mixer to obtain a moldable rock wool fiber-based slurry, pour the rock wool fiber-based slurry on the bonding layer, expel bubbles by vibration molding, let it stand for 4 hours for initial setting, and obtain a composite board green body;

[0045] Step S4. Place the green composite board into a sintering furnace for sintering to obtain a finished ceramic-based rock wool composite board, wherein the sintering system is to first heat the temperature from room temperature to 200°C at a heating rate of 1°C / min and keep warm for 1 hour; then heat the temperature from 200°C to 500°C at a heating rate of 2°C / min and keep warm for 2 hours; then heat the temperature from 500°C to 800°C at a heating rate of 5°C / min and keep warm for 1 hour; then heat the temperature from 800°C to 1250°C at a heating rate of 2°C / min and keep warm for 3 hours; and finally, cool to room temperature with the furnace.

[0046] Example 3

[0047] Embodiment 3 provides a high-temperature ceramic-based rock wool composite board and a preparation process thereof, wherein:

[0048] The high-temperature ceramic-based rock wool composite board comprises a ceramic base layer, a bonding layer and a rock wool fiber layer, wherein the thickness ratio among the ceramic base layer, the bonding layer and the rock wool fiber layer is 5:1.5:4.

[0049] Step S1. Prepare a ceramic base: weigh 50 parts of waste ceramic powder, 10 parts of high-alumina cement and 20 parts of rock wool fiber according to the formula, mix the above raw materials in a blender to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use vibration molding to expel bubbles, let it stand for 4 hours for initial setting, and obtain a preliminarily shaped green body;

[0050] Step S2. Prepare a bonding layer: according to the formula, weigh 60 parts of aluminum phosphate and 30 parts of rock wool fiber and stir to form a bonding slurry, and apply the bonding slurry on the preliminarily shaped green body to form a bonding layer;

[0051] Step S3. Prepare a rock wool fiber layer: weigh 50 parts of rock wool fiber, 5 parts of high-alumina cement and 10 parts of waste ceramic powder according to the formula, mix the above raw materials in a mixer to obtain a moldable rock wool fiber-based slurry, pour the rock wool fiber-based slurry on the bonding layer, expel bubbles by vibration molding, let it stand for 4 hours for initial setting, and obtain a composite board green body;

[0052] Step S4. Place the composite board green body into a sintering furnace for sintering to obtain a finished ceramic-based rock wool composite board product, wherein the sintering system is firstly to heat up from room temperature to 200°C at a heating rate of 2°C / min and keep warm for 2h, then to heat up from 200°C to 500°C at a heating rate of 2°C / min and keep warm for 2h, then to heat up from 500°C to 800°C at a heating rate of 2°C / min and keep warm for 1h, then to heat up from 800°C to 1250°C at a heating rate of 2°C / min and keep warm for 3h, and finally, cool to room temperature with the furnace.

[0053] Example 4

[0054] Embodiment 4 provides a high-temperature ceramic-based rock wool composite board and a preparation process thereof, wherein:

[0055] The high-temperature ceramic-based rock wool composite board comprises a ceramic base layer, a bonding layer and a rock wool fiber layer, wherein the thickness ratio among the ceramic base layer, the bonding layer and the rock wool fiber layer is 5:1.5:3.

[0056] Step S1. Prepare a ceramic base: weigh 70 parts of waste ceramic powder, 20 parts of high-alumina cement and 30 parts of rock wool fiber according to the formula, mix the above raw materials in a mixer to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use vibration molding to expel bubbles, let it stand for 2 hours for initial setting, and obtain a preliminarily shaped green body;

[0057] Step S2. Prepare a bonding layer: according to the formula, weigh 60 parts of aluminum phosphate and 30 parts of rock wool fiber and stir to form a bonding slurry, and apply the bonding slurry on the preliminarily shaped green body to form a bonding layer;

[0058] Step S3. Prepare a rock wool fiber layer: weigh 60 parts of rock wool fiber, 6 parts of high-alumina cement and 15 parts of waste ceramic powder according to the formula, mix the above raw materials in a mixer to obtain a moldable rock wool fiber-based slurry, pour the rock wool fiber-based slurry on the bonding layer, expel bubbles by vibration molding, let it stand for 2 hours for initial setting, and obtain a composite board green body;

[0059] Step S4. Place the green composite board into a sintering furnace for sintering to obtain a finished ceramic-based rock wool composite board, wherein the sintering system is to first heat the temperature from room temperature to 200°C at a heating rate of 2°C / min and keep warm for 1 hour; then heat the temperature from 200°C to 500°C at a heating rate of 3°C / min and keep warm for 1 hour; then heat the temperature from 500°C to 800°C at a heating rate of 2°C / min and keep warm for 1 hour; then heat the temperature from 800°C to 1250°C at a heating rate of 3°C / min and keep warm for 1 hour; and finally, cool to room temperature with the furnace.

[0060] Example 5

[0061] Example 5 provides a high-temperature ceramic-based rock wool composite board and a preparation process thereof, wherein:

[0062] The high-temperature ceramic-based rock wool composite board comprises a ceramic base layer, a bonding layer and a rock wool fiber layer, wherein the thickness ratio among the ceramic base layer, the bonding layer and the rock wool fiber layer is 5:1.0:4.

[0063] Step S1. Prepare a ceramic base: weigh 60 parts of waste ceramic powder, 15 parts of high-alumina cement and 30 parts of rock wool fiber according to the formula, mix the above raw materials in a mixer to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use vibration molding to expel bubbles, let it stand for 2 hours for initial setting, and obtain a preliminarily shaped green body;

[0064] Step S2. Prepare a bonding layer: according to the formula, weigh 60 parts of aluminum phosphate and 10 parts of rock wool fiber and stir to form a bonding slurry, and apply the bonding slurry on the preliminarily shaped green body to form a bonding layer;

[0065] Step S3. Prepare a rock wool fiber layer: weigh 50 parts of rock wool fiber, 10 parts of high-alumina cement and 15 parts of waste ceramic powder according to the formula, mix the above raw materials in a mixer to obtain a moldable rock wool fiber-based slurry, pour the rock wool fiber-based slurry on the bonding layer, expel bubbles by vibration molding, let it stand for 2 hours for initial setting, and obtain a composite board green body;

[0066] Step S4. Place the composite board green body into a sintering furnace for sintering to obtain a finished ceramic-based rock wool composite board product, wherein the sintering system is firstly to heat up from room temperature to 200°C at a heating rate of 2°C / min and keep warm for 1h, then to heat up from 200°C to 500°C at a heating rate of 3°C / min and keep warm for 1h, then to heat up from 500°C to 800°C at a heating rate of 4°C / min and keep warm for 1h, then to heat up from 800°C to 1250°C at a heating rate of 4°C / min and keep warm for 1h, and finally, cool to room temperature with the furnace.

[0067] Examples 6 to 9

[0068] The difference between Examples 6 to 9 and Example 5 is that the ratio of aluminum phosphate to rock wool fiber is different, as shown in the following table.

[0069] Table 2 shows the ratio of aluminum phosphate to rock wool fiber in Examples 5 to 9

[0070] Example Example 5 Example 6 Example 7 Example 8 Example 9 Proportion 6:1 6:2 6:3 6:4 6:5

[0071] Comparative Example 1

[0072] The difference between this control example and Example 2 is that step S2 is omitted, and the rock wool fiber layer prepared in step S3 is directly covered on the ceramic base layer prepared in step S1.

[0073] Performance testing method:

[0074] Test method for interlayer bonding strength: The specimen is usually cut into standard size (such as 50mm×50mm) and fixed in a special fixture. The shear strength value (τ=F max / A), this method can effectively quantify the interlayer bonding force.

[0075] Interlaminar cracking test method: The sample is placed in a high-temperature furnace and subjected to multiple cycles of heating and cooling in the range of 800℃ to 1200℃ (e.g., high temperature is maintained for 1 hour and then rapidly cooled to room temperature). After multiple cycles, the change in interlaminar bonding strength is re-evaluated through a shear test, and whether there is crack extension or interlaminar failure is observed.

[0076] Preparation of XRD samples: Accurately extract the middle layer sample from the sintered composite plate, separate it along the interlayer interface using a precision cutter, and lightly grind the collected samples to remove the attached ceramic base or rock wool fiber layer materials to ensure the purity of the samples. Subsequently, the middle layer sample is ground into powder using a mortar or ball mill, and the particle size is controlled to be less than 75μm (below 200 mesh sieve) to meet the particle size requirements of XRD analysis, and the segregation phenomenon in the sample is reduced by sufficient mixing. In the film-making stage, the evenly distributed powder is loaded into the XRD sample stage, gently compacted to ensure a smooth surface, and the interference of the particle orientation effect on the results is reduced by gently vibrating the sample stage. Finally, set appropriate scanning conditions in the XRD test (such as 2θ=10°~80°, scanning speed 2° / min).

[0077] Table 3 shows the performance characteristics of the ceramic-based rock wool composite board prepared in Examples 1 to 9

[0078]

[0079]

[0080] Combined with Example 2 and Figure 1 It can be seen that the composite sheet prepared by the preparation process of this embodiment has a plurality of new phases in the intermediate bonding layer, which mainly include aluminum phosphate (AlPO4), calcium aluminum phosphate (CaAlPO4), phosphate glass phase, and possibly a small amount of mullite (3Al2O3·2SiO2) and calcium feldspar (CaAl2Si2O8). Aluminum phosphate is the main phase of the bonding layer, providing high-temperature structural stability and excellent interface bonding performance. Calcium aluminum phosphate enhances the high-temperature mechanical properties of the bonding layer, while effectively alleviating the interfacial stress caused by the difference in thermal expansion coefficients between the ceramic base layer and the rock wool fiber layer. The phosphate glass phase improves the compactness of the bonding layer by filling the interface micropores and provides good thermal stress buffering capacity. In addition, a small amount of mullite and calcium feldspar further enhances the crack resistance and mechanical strength of the bonding layer. The synergistic effect of these new phases not only enables the bonding layer to have a good bonding effect in the composite sheet, but also significantly improves the overall thermal stability and crack resistance of the composite sheet.

[0081] Combining Examples 1 to 4 and Table 3, it can be seen that Examples 1 to 4 exhibit excellent bonding strength, with interlayer bonding strength reaching 22.3 MPa to 25.6 MPa, and maintained at 15.9 MPa to 19.8 MPa after multiple thermal cycles, showing good interface stability and thermal expansion matching capabilities. Examples 1 to 4 did not experience interface cracking after multiple thermal cycles, indicating that the optimized bonding layer formula and thickness design effectively alleviated the difference in thermal expansion coefficients between the ceramic base layer and the rock wool fiber layer.

[0082] Combining Example 2, Comparative Example 1 and Table 3, it can be seen that the composite sheet of Example 2 is significantly better than that of Comparative Example 1 in interlayer bonding strength and thermal cycle stability. The initial interlayer bonding strength of Example 2 is 24.8MPa, which is much higher than 18.5MPa of Comparative Example 1, which shows that the optimized bonding layer formula significantly improves the initial bonding force. After multiple thermal cycles, the interlayer bonding strength of Example 2 remains at 18.7MPa, showing good thermal stability and interface bonding strength, while the bonding strength of Comparative Example 1 under the same conditions drops significantly to only 10.2MPa, and the interface cracks, showing poor resistance to thermal stress. This is mainly because during the high-temperature sintering process (800 to 1300°C), the hydration products of high-aluminum cement decompose and generate high-temperature phases such as calcium aluminate (CA) and calcium aluminum spinel (CA6), which react synergistically with aluminum phosphate to generate a variety of new phases such as aluminum phosphate (AlPO4), calcium aluminum phosphate (CaAlPO4), etc. These newly generated phases have good thermal stability and chemical durability, and are distributed at the interface in the form of glass phase or semi-crystalline phase, which not only fills microcracks and pores, but also forms a "bridge" at the microstructural level, greatly enhancing the interlayer bonding force. Moreover, on the one hand, these new phases usually have a thermal expansion coefficient between the ceramic matrix and the rock wool fiber matrix, playing the role of a "transition layer", gradually adjusting the thermal expansion gradient between the two materials in the microstructure, reducing the shear stress or tensile stress caused by expansion mismatch, and on the other hand, the glass phase in the new phase has a certain viscosity at high temperature, which can absorb and disperse local stress, and at the same time, fill the interface microcracks by penetration, prevent crack propagation and enhance interface density. In addition, the viscosity and partial liquid properties of aluminum phosphate at high temperature can buffer the interface stress concentration caused by the difference in thermal expansion coefficients between the ceramic matrix and the rock wool fiber gene, thereby reducing the risk of peeling or cracking.

[0083] It can be seen from Examples 5 to 9 and Table 3 that as the content of rock wool fiber gradually increases, the interlayer bonding force shows a trend of increasing first and then decreasing. In Examples 5 to 7, as the content of rock wool fiber increases, the interlayer bonding force gradually increases, reaching a maximum value (26.9MPa) in Example 7. This phenomenon shows that an appropriate amount of rock wool fiber can effectively fill the micropores and defects in the bonding layer to form a uniformly distributed fiber network structure, which not only improves the density and structural uniformity of the bonding layer, but also provides good mechanical support during high-temperature sintering. At the same time, rock wool fiber interacts with inorganic gelling materials such as aluminum phosphate to generate stable new phases such as aluminum phosphate (AlPO4) and calcium aluminum phosphate (CaAlPO4) at high temperatures. These phases further enhance the interfacial chemical bonding force, fill the interfacial microcracks, and improve the overall bonding performance. In addition, the lower thermal expansion coefficient of rock wool fiber forms a good thermal expansion match with the inorganic components in the bonding layer, which can effectively buffer the thermal expansion difference between the ceramic base and the rock wool fiber layer, and reduce the risk of interfacial stress concentration and cracking during thermal cycling. However, when the content of rock wool fiber continues to increase (such as Example 8 and Example 9), the interlayer bonding force gradually decreases, and drops to 21.7MPa in Example 9. This may be due to the fact that the excessively high content of rock wool fiber leads to uneven fiber distribution in the bonding layer, forming local agglomerations, which reduces the overall uniformity and density of the bonding layer. In addition, the excessive amount of rock wool fiber may dilute the proportion of inorganic gelling materials such as aluminum phosphate in the bonding layer, reduce the formation of new phases such as aluminum phosphate (AlPO4) and calcium aluminum phosphate (CaAlPO4) during high-temperature sintering, and thus affect the chemical bonding strength of the interface.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation process of a high-temperature ceramic-based rock wool composite board, characterized in that: The technical steps include: Step S1. Prepare a ceramic base layer: weigh ceramic powder, a first inorganic gelling material and rock wool fiber according to a formula, mix the above raw materials in a blender to obtain a moldable ceramic-based slurry, evenly spread the ceramic-based slurry in a mold, use a vibration molding method to expel bubbles, let it stand for 2 to 4 hours for initial setting, and obtain a preliminarily shaped green body; Step S2. preparing a bonding layer: weighing a second inorganic gelling material and rock wool fibers according to a formula, stirring to form a bonding slurry, and coating the bonding slurry on the preliminarily shaped green body to form a bonding layer; Step S3. Preparing a rock wool fiber layer: weighing rock wool fibers, a first inorganic gelling material and a ceramic powder according to a formula, mixing the above raw materials in a blender to obtain a moldable rock wool fiber-based slurry, pouring the rock wool fiber-based slurry on the bonding layer, expelling bubbles by vibration molding, standing for 2 to 4 hours for initial setting, and obtaining a composite board green body; Step S4: placing the green composite board into a sintering furnace for sintering to obtain a finished ceramic-based rock wool composite board.

2. The preparation process of the high temperature ceramic-based rock wool composite board according to claim 1, characterized in that: The first inorganic gelling material is high alumina cement, and the second inorganic gelling material is aluminum phosphate.

3. The preparation process of the high temperature ceramic-based rock wool composite board according to claim 1, characterized in that: In step S1, the ceramic powder is 50 to 70 parts, the first inorganic gelling material is 10 to 20 parts, and the rock wool fiber is 15 to 30 parts.

4. The preparation process of the high temperature ceramic-based rock wool composite board according to claim 1, characterized in that: In step S2, the second inorganic gel material is 60 parts, and the rock wool fiber is 10 parts to 50 parts.

5. The preparation process of the high temperature ceramic-based rock wool composite board according to claim 1, characterized in that: In step S3, the rock wool fiber is 40 to 60 parts, the first inorganic gelling material is 5 to 10 parts, and the ceramic powder is 10 to 20 parts.

6. The preparation process of the high temperature ceramic-based rock wool composite board according to claim 1, characterized in that: In step S4, the sintering system is firstly to heat up from room temperature to 200°C at a heating rate of 1 to 2°C / min and keep warm for 1 to 2h, then to heat up from 200°C to 500°C at a heating rate of 2 to 3°C / min and keep warm for 1 to 2h, then to heat up from 500°C to 800°C at a heating rate of 2 to 5°C / min and keep warm for 1h, then to heat up from 800°C to 1250°C at a heating rate of 2 to 4°C / min and keep warm for 1 to 3h, and finally, cool to room temperature with the furnace.

7. The preparation process of the high temperature ceramic-based rock wool composite board according to claim 1, characterized in that: The ceramic powder is waste ceramic powder.

8. A composite board prepared by the preparation process according to any one of claims 1 to 7, characterized in that: The composite plate comprises a ceramic base layer, a bonding layer and a rock wool fiber layer.

9. The composite sheet material according to claim 8, characterized in that: The thickness ratio between the ceramic base layer, the bonding layer and the rock wool fiber layer is (4 to 6): (0.5 to 1.5): (3 to 5).

Citation Information

Patent Citations

  • High-strength fireproof rock wool board and preparation method thereof

    CN118560111A